Mechanical properties of concrete reinforced with hybrid polypropylene- PET waste fibers - Hussein, Sary N.; Mohammed, Azad A. (Sulaimani Journal for Engineering Sciences, 2021)
In this article, flexural strength and compressive strength of concrete containing polypropylene fiber (PP), polyethylene terephthalate (PET) waste fiber and a combination between them were experimentally investigated. For this reason, laboratory experiments were performed on a total of 40 mixes. Results show that compressive strength property of concrete reinforced with PET waste fiber is not comparable to that of concrete reinforced with PP fiber, in which there is a compressive strength reduction, and the effect of PET fiber length on the strength is not important. Behavior of concrete contained PET waste fiber in flexure was found better. There is a good opportunity to use a hybrid fiber (25% PET and 75% PP) to enhance flexural strength of concrete.
Keywords: Compressive strength; Flexural strength; PET waste fiber; Polypropylene fiber; Hybrid fiber